A Mobile Application For Healthcare Self-Monitoring - Chua, Tian Foo; Ishak, Suhaimi (Applied Information Technology And Computer Science, 2023)
A mobile application for healthcare self-monitoring is an application built and developed to help the general people communicate more efficiently with medical professionals. This mobile application was created to enable the general public to receive customized services or consultations from medical professionals. Obtaining the service is time-consuming and inefficient, and there is no dedicated platform for communication between users and medical professionals. The Agile software development technique was used to create the project. The Firebase database and Android Studio tools are used to create the application. After the implementation phase, the functional testing and User Acceptance Testing were built. Overall, this mobile application might provide a specific platform for users and medical experts to communicate and share accurate healthcare information.